The Innovation of Democratic Education: The Development of Learning Approach Based on the Sutan Syahrir’ Thought to Strengthen Students’ Democratic Attitude - Adi Setiawan; Sariyatun Sariyatun; Deny Tri Ardianto (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2018)
In the recent years, the topic of democracy has become important issues for Indonesian society. The designed curriculum and learning practices should be integrated with the thoughts of our founding fathers that reflect the values of democratic attitude. Sutan Syahrir as one of our founding fathers who gave his thoughts in settling the new direction about the democratic state after the Indonesian independence. Sutan Syahrir explains the concept of humanism in the freedom, equality, collectivity, the equality between right and responsibilities. The discussion of Sutan Syahrir’s thoughts can be extended to the issues of contemporary education. The authors argue that Sutan Syahrir’s thought can be used to develop the innovative learning based on the values of democracy. This article aims to give a conceptual framework of innovative learning about the Sutan Syahrir’s thought to improve the students’ democratic attitude.